The IAU Office of Astronomy for Development. (5th March 2015) - Govender, Kevin
Abstract: The IAU Office of Astronomy for Development (OAD)†, established in March 2011 as part of the implementation of the IAU Strategic Plan, is currently located in South Africa and serves as a global coordinating centre for astronomy-for-development activities. In terms of structure the OAD is required to establish regional nodes (similar offices in different parts of the world which focus on a particular geographic or cultural region) and three task forces: (i) Astronomy for Universities and Research, (ii) Astronomy for Children and Schools, and (iii) Astronomy for the Public. This paper will describe the progress of the OAD towards the realisation of the vision 'Astronomy for a better world'.